PENGARUH DINAMIKA DAN KEMANDIRIAN KELOMPOK PEMBUDIDAYA IKAN (POKDAKAN) TERHADAP KEBERHASILAN USAHA BUDI DAYA IKAN NILA (OREOCHROMIS NILOTICUS) (Suatu Kasus Di Kota Sukabumi) - Gilang Aulia; Euis Dasipah; Nendah Siti Permana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Aquaculture business in Sukabumi City is a small-scale business, so there are still various problems that can hinder business development. By joining the group, it is hoped that it will have a real influence on the empowerment of fish farmers, especially in increasing production and independence of fish farmers in making decisions. This study aims to determine the combined effect of group dynamics and independence, the influence of each, as well as the relationship between group dynamics and independence on the success of tilapia aquaculture in the Fish Farmers Group (Kelompok Pembudidaya Ikan) in the city of Sukabumi. The study was conducted in Sukabumi City in November 2021 - March 2022 with the subject of the analysis being Pokdakan which farming tilapia as many as 49 people. The research variables are Group Dynamics (X1), Group Independence (X2) and Business Success (Y). The results shows that the direct influence of group dynamics and group independence on business success was 34%. Group dynamics have no significant effect on business success, the direct effect is only 3.13%. Group independence has a significant effect on business success, with an effect of 20.89%. Group dynamics and group self-reliance have a significant and positive relationship.